The European Union's industrial policy: What are the main challenges? - Michael Landesmann; Roman Stöllinger (The Vienna Institute for International Economic Studies (wiiw), 2020)
This policy report stakes a stance on industrial policy in the European Union in the light of the revived interest in the subject and the most pressing challenges ahead. In the current global context these challenges are: (i) to keep pace at the technology frontier with the technologically most advanced economies; (ii) to meet the challenge of fast catching-up emerging economies; (iii) to contribute to the convergence and cohesion processes within the EU; and (iv) to deal with climate change and environmental sustainability issues more generally. A quantitative exercise that makes use of the EU's budget data, including the structural funds, and member states state aid expenditures is used to identify the EU's current industrial policy priorities. The results are the basis for an assessment of the extent to which the key challenges are addressed at the supranational level and which aspects are primarily dealt with by national governments.
Keywords: L5; L16; O25; O38; O52; Q59; F68; 330; Industrial policy; EU's industrial policy; smart specialisation; mission-oriented industrialpolicy; EU structural funds; EU cohesion policy; EU competitiveness; EU Green Deal